Students' Perception of Interactive Read-Aloud Strategies in Learning Narrative Texts - Putri, Tiara; Rahmawati, Maya; Kartini, Dedeh (Journal of Educational Sciences, 2025)
This study aims to describe students' perceptions of the implementation of interactive read-aloud strategy in learning narrative text. This research used a qualitative approach with a case study design. The participants were one ninth grade class from a junior high school located in Karawang. Data were obtained through interviews with six students as well as observation during the learning process. The interviews were conducted after the implementation of interactive read-aloud strategy. The results showed that students' perceptions responded positively to the implementation of the interactive read-aloud strategy. There are three main findings related to students' perceptions: first, the Interactive Read-Aloud strategy helps students in understanding narrative text; second, the strategy makes the learning process more fun and interesting; and third, the strategy encourages students' active involvement in learning. Therefore, Interactive Read-Aloud plays an important role in creating an interactive learning environment and motivating students to be more engaged. Thus, this strategy is very useful and suitable to be applied to ninth grade students.